PERCEIVED PARENTING STYLES AND MALADJUSTMENT IN PEDIATRIC CHILDREN. - López-Soler, Concepción; Puerto, Jean Carlos; López Pina, José Antonio; Prieto, Macarena (Anales de Psicología / Annals of Psychology, 2009)
This paper presents the results of a study with a sample of 103 children between 8 and 12 years old who completed the Test Autoevaluativo Multifactorial de Adaptación Infantil. The aim of this study was to examine the relationships among personal and social maladjustment and the perceived parenting styles, and also to determine child gender differences. Using four regression analyses we tried to examine the relationships between Personal and Social maladjustment scales and the Customized education (Authoritative style), Permissiveness (Permissive style) and Restriction (Authoritarian style). The results demonstrated that Authoritarian style has a positive relationship with personal and social maladjustment in boys and girls.